2006
DOI: 10.1007/s10584-006-9054-1
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Using Global Warming Potentials: Analysing the Trade off Between CO2, CH4 and N2O

Abstract: Abstract. The metric governing the trade-off between different greenhouse gases in the Kyoto Protocol, the Global Warming Potentials (GWPs), has received ample critique from both scientific and economic points of view. Here we use an integrated climate-economic optimization model to estimate the cost-effective trade-off between CO 2 , CH 4 and N 2 O when meeting a temperature stabilization target. We then estimate the increased cost from using GWPs when meeting the same temperature target. Although the efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 39 publications
2
73
0
Order By: Relevance
“…2 Imperfect though it might be, it still achieves an important role in allowing the implementation of the Kyoto Protocol and there would undoubtedly be a cost to changing the method of calculating CO 2 -equivalence; importantly, if there was to be a change, it would need to be done with good cause, it would require widespread consensus, it would need to be suited to the climate policy that it is meant to serve and it would have to have some degree of permanence. Further, as shown by Johansson et al (2006) (see also O'Neill 2003), integrated climate-economic models indicate a large economic benefit in adopting a multi-gas approach rather than a CO 2 -only approach in meeting some specified temperature stabilization approach; however, they also show that there is relatively little economic penalty in adopting the GWP to calculate CO 2 -equivalence, rather than using their optimised approach (at least on a global level-this may not be true for individual nations).…”
mentioning
confidence: 78%
“…2 Imperfect though it might be, it still achieves an important role in allowing the implementation of the Kyoto Protocol and there would undoubtedly be a cost to changing the method of calculating CO 2 -equivalence; importantly, if there was to be a change, it would need to be done with good cause, it would require widespread consensus, it would need to be suited to the climate policy that it is meant to serve and it would have to have some degree of permanence. Further, as shown by Johansson et al (2006) (see also O'Neill 2003), integrated climate-economic models indicate a large economic benefit in adopting a multi-gas approach rather than a CO 2 -only approach in meeting some specified temperature stabilization approach; however, they also show that there is relatively little economic penalty in adopting the GWP to calculate CO 2 -equivalence, rather than using their optimised approach (at least on a global level-this may not be true for individual nations).…”
mentioning
confidence: 78%
“…Some analyses have suggested that the GWP concept does not lead to economically optimal greenhouse-gas mitigation strategies [12], and the basis for comparisons between gases has also been dealt with more directly in terms of the economic implications of managing future emissions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Emissions of carbon dioxide, methane and nitrous oxide are determined endogenously in the model so as to minimize the net present value abatement cost of stabilizing the global average surface temperature at 2 K above the pre-industrial level. The trade-offs among the different greenhouse gases are not constrained by their Global Warming Potentials (GWPs); the abatement of the emissions of each gas is determined to achieve the lowest cost of temperature stabilization; see Manne and Richels (2001) and Johansson et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…The numerical model is an updated version of the MiMiC model presented and used in Johansson et al (2006Johansson et al ( , 2008. The main differences between the model used here and the versions in Johansson et al (2006Johansson et al ( , 2008 are that the energy balance model has been improved (by the use of a three-box energy balance model that is calibrated to an upwelling-diffusion energy balance model), the carbon cycle representation has been recalibrated, climate-feedbacks in the carbon cycle are taken into account, and updated data have been used to initialize and fit the model to the historical global average radiative forcing and surface temperature levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation